Pancreatic Stellate Cells: A Rising Translational Physiology Star as a Potential Stem Cell Type for Beta Cell Neogenesis - Zhou, Yunting; Sun, Bo; Li, Wei; Zhou, Junming; Gao, Feng; Wang, Xiaohang; Cai, Min; Sun, Zilin (Frontiers in Physiology, 2019)
The progressive decline and eventual loss of islet β-cell function underlies the pathophysiological mechanism of the development of both type 1 (T1D) and type 2 diabetes (T2D). The recovery of functional β-cells is an important strategy for the prevention and treatment of diabetes. Based on similarities in developmental biology and anatomy, in vivo induction of differentiation of other types of pancreatic cells into β-cells is a promising avenue for future diabetes treatment. Pancreatic stellate cells (PSCs), which have attracted intense research interest due to their effects on tissue fibrosis over the last decade, express multiple stem cell markers and can differentiate into a number of cell types. In particular, PSCs can successfully differentiate into insulin-producing cells in vitro and can contribute to organ regeneration. In this review, we will summarize the latest progress and knowledge of the translational physiology potential of PSCs and discuss ways to facilitate the future development of this often controversial but crucial research.